Eating only the same food: How health concerns and gender influence food neophobia - Ratriningtyas, Chelinta Dyah Arum; Undarwati, Anna (Jurnal Psikologi Terapan dan Pendidikan, 2025)
Food neophobia is an aversion to and avoidance of new foods, a phenomenon that can significantly influence dietary patterns and food choices throughout the lifespan. Food neophobia is thought to be influenced by personal factors, such as health concerns and gender. The purpose of this study was to determine the influence of health concerns and gender on food neophobia, with the hypothesis that both factors affect it. This study employed a cross-sectional design with participants aged 18–25 years. Data were collected using the Health Concern Scale and the Food Neophobia Scale, which were distributed via various social media platforms. A univariate general linear model was conducted to identify the influence of independent variables on food neophobia. The results indicate that health concerns positively influence food neophobia, whereas gender does not moderate the relationship between health concerns and food neophobia. These findings can serve as a basis for developing psychological interventions tailored to individuals with food neophobia based on their level of health concern.